Answer:
Third one I believe
Step-by-step explanation:
The correct answer is B)x =
.
In order to find this, we need for follow the order of operations.
y - p = m(x - q) ----> Divide both sides by m
= x - q ----> add q to both sides
= x ---> now we need to give it a common denominator. Multiply the q term by m/m
= x
This is our final answer.
Answer:
Step-by-step explanation:

The answer is bbc or if that’s not the answer the then it’s bbl THANK ME LATERRRR
It's the third one. It is the correct option.